2009
DOI: 10.1094/phyto-99-7-0802
|View full text |Cite
|
Sign up to set email alerts
|

Internal Resistance in Winter Oilseed Rape Inhibits Systemic Spread of the Vascular Pathogen Verticillium longisporum

Abstract: Verticillium longisporum is a vascular fungal pathogen presently threatening oilseed rape production in Europe. Systemic spread and vascular responses were studied in a susceptible ('Falcon') and a resistant genotype (SEM 05-500256) of Brassica napus. Colonization of both genotypes after dip-inoculation of the roots followed by quantitative polymerase chain reaction revealed similarities only in the initial stages of root penetration and colonization of the hypocotyl, while a substantial invasion of the shoot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 50 publications
6
96
0
4
Order By: Relevance
“…Studies comparing resistant and susceptible cultivars of pepper, cotton, cauliflower, broccoli and tomato provided evidence that peroxidases and increased lignification are involved in the defense against V. dahliae and V. albo-atrum [21], [54][58]. Similarly, Eynck et al [59] found that cell wall re-inforcement and lignification in the hypocotyl limited the spread of V. longisporum in a resistant cultivar of B. napus , although the fungus was able to colonize the roots of both cultivars. Our data indicate that these defenses are also activated in VL-infected Arabidopsis .…”
Section: Discussionmentioning
confidence: 92%
“…Studies comparing resistant and susceptible cultivars of pepper, cotton, cauliflower, broccoli and tomato provided evidence that peroxidases and increased lignification are involved in the defense against V. dahliae and V. albo-atrum [21], [54][58]. Similarly, Eynck et al [59] found that cell wall re-inforcement and lignification in the hypocotyl limited the spread of V. longisporum in a resistant cultivar of B. napus , although the fungus was able to colonize the roots of both cultivars. Our data indicate that these defenses are also activated in VL-infected Arabidopsis .…”
Section: Discussionmentioning
confidence: 92%
“…dahlia [47]. Similarly, lignin might be important at later infection stages, whereas the soluble and cell wall-bound phenolics seem to be involved in the early defense against the fungus [48], which could oxidize phenolic compounds into quinones to inhibit pathogen, and improve the resistance of plants.…”
Section: Discussionmentioning
confidence: 99%
“…For distal tissues, phenolic compounds were measured in leaves of plants grown for 5 weeks in the sterile systemic hydroponic system, in which roots were pretreated with oxo-C14-HSL for 3 d and leaves subsequently challenged with 1 mM flg22 for 24 h. Samples were taken 0 and 24 h after challenge, freeze-dried, and crushed with metal beads in a TissueLyser. All phenolic compounds were measured via a colorimetric assay based on the Folin-Ciocalteau method (Eynck et al, 2009) with some modifications. The soluble phenolic compounds were extracted twice with 80% aqueous methanol for 1 h. The phenolic compounds were measured in the merged supernatants.…”
Section: Phenolic Compound Extractionmentioning
confidence: 99%